2017
DOI: 10.1177/0170840616685361
|View full text |Cite
|
Sign up to set email alerts
|

Being an Early-Career CMS Academic in the Context of Insecurity and ‘Excellence’: The Dialectics of Resistance and Compliance

Abstract: Drawing on a dialectical approach to resistance, we conceptualise the latter as a multifaceted, pervasive and contradictory phenomenon. This enables us to examine the predicament in which early-career Critical Management Studies (CMS) academics find themselves in the current times of academic insecurity and 'excellence', as gleaned through this group's understandings of themselves as resisters and participants in the complex and contradictory forces constituting their field. We draw on 24 semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(183 citation statements)
references
References 58 publications
2
175
2
4
Order By: Relevance
“…As we well know, the academy is just as heavily implicated in the economics and politics of neoliberalism as any other work sphere. Higher education (and the research that takes place therein) is increasingly subject to commodification and creeping managerialism (Bristow et al, 2017;Butler & Spoelstra, 2012;Heller, 2016;Parker, 2014). A culture of enterprise increasingly pervades the groves of academe, with researchers subject to increasingly instrumental metrics.…”
Section: Questions and Provocations: The Future Of Resistance Studiesmentioning
confidence: 99%
“…As we well know, the academy is just as heavily implicated in the economics and politics of neoliberalism as any other work sphere. Higher education (and the research that takes place therein) is increasingly subject to commodification and creeping managerialism (Bristow et al, 2017;Butler & Spoelstra, 2012;Heller, 2016;Parker, 2014). A culture of enterprise increasingly pervades the groves of academe, with researchers subject to increasingly instrumental metrics.…”
Section: Questions and Provocations: The Future Of Resistance Studiesmentioning
confidence: 99%
“…Constructing a CMS ECA identity [Critical Management Studies Early Career Academic]-today necessitates perennial, contingent and highly nuanced work of resistance and compliance that continuously calls for creativity, inventiveness, courage, political astuteness and reflexivity as an integral part of the role of this group of academics within the management studies field (Bristow et al, 2017(Bristow et al, : 1187. Robinson et al, (2017: 496) have also found that CMS ECA have developed an ability to read, resist and play such demands.…”
Section: Struggling With Health Within the Neoliberal Academymentioning
confidence: 99%
“…More specifically, much like medical researchers may focus on 'high risk' groups, we focus on the margins of business schools, where the impact of the changes has arguably been particularly profound (Huzzard, Benner, & Kärreman, 2017;Mingers & Willmott, 2013). Our research participants work on multiple business school peripheries -in terms of career stage, nonmainstream CMS approaches that are often at odds with the business school ethos (Butler & Spoelstra, 2014), and often geography too -that make them more vulnerable but potentially more reflexive about the HE system (Bristow, Robinson, & Ratle, 2017). Analysing their experiences in conjunction with previous literature on academic labor (e.g.…”
Section: Alexandra Bristow Sarah Robinson and Olivier Ratlementioning
confidence: 99%
“…The 'make-or-break' stage of their career means that their identities as academics are in a particularly intensive and vulnerable period of construction (Laudel & Gläser, 2008;Smith, 2010. Their CMS ethos also places them in an extra insecure position on the margins of business schools (Bristow et al, 2017) and slows down the pace of their identity work vis-à-vis performance measures. It often puts them at odds with business school managerialism thus requiring creative rhythm-identity workarounds leading to further polyrhythmia and arrhythmia.…”
Section: Alexandra Bristow Sarah Robinson and Olivier Ratlementioning
confidence: 99%